Intoxicação espontânea e experimental por Crotalaria spectabilis (Fabaceae) em bovinos - Ribeiro, Marlon (2020)
Epidemiological, clinical and morphological findings of spontaneous and experimental poisoning by Crotalaria spectabilis in bovines were described. Spontaneous intoxication occurred in a farm in the municipality of Sapezal, Mato Grosso (MT), 20 days after the introduction bovines in a pasture invaded by C. spectabilis, six cattle were affected and died and one of them was submitted to necropsy. After this, the remai ing cattle in that pasture were transferred to a property in the municipality of São José do Rio Claro, MT. In this farm, 45 days, after the bovines were transported, 35 of them were sick, 15 died and 2 was submitted to necropsy. . The sick bovines showed weight loss, jaundice, recumbence, pedaling movements and death. The main macroscopic changes were observed in the liver and were firm and yellowish iirregular areas. Microscopically, hepatic findings were fibrosis, , megalocytosis, microvacuolar degeneration and cholestasis. Vascular lesions with different intensities were observed in the lungs and kidney of three cattle. There was status soongiosus in two cattle. The disease was experimentally reproduced in cattle through administration via oral of seeds of Crotalaria espectabilis at a dose of 1g / kg / day for 30 days. Clinical signs were observed 87 days after ingestion of the first dose and death occurred two days after the onset of clinical signs in both animals. The clinical and macroscopic signs observed were similar to those observed in spontaneous intoxication.